EFFECT OF TEMPERATURE AND SPEED OF STIRRER TO BIODIESEL CONVERSION FROM COCONUT OIL WITH THE USE OF PALM EMPTY FRUIT BUNCHES AS A HETEROGENEOUS CATALYST - Luthfi Pratama; Yoeswono Yoeswono; Triyono Triyono; Iqmal Tahir (Indonesian Journal of Chemistry, 2009)
Biodiesel synthesis by transesterification reaction of coconut oil with methanol by using ash of palm empty fruit bunches (EFB) as base catalyst has been conducted. Sample of ash was prepared through heating, screening, reashing, and finally determining of potassium content. Sample of coconut oil was analyzed by GC-MS. A certain amount of ash was extracted in methanol with mixing for about 1 h at room temperature and a result was used for reaction of transesterification. The studied variables were effect of temperature and speed of stirrer. The composition of the methyl esters (biodiesel) was analyzed using GC-MS and 1H NMR, whereas characters of biodiesel were analyzed using ASTM methods. The results showed that potassium content in ash of EFB could be extracted by methanol and it could be used as base catalyst in the biodiesel synthesis. The value increasing of both variables enhanced the biodiesel conversion. The properties of biodiesel were relatively conformed to specification of biodiesel.